The anatomical evolution of the thyroid cartilage from childhood to adulthood: A computed tomography evaluation. (13th June 2017) - Glikson, Eran; Sagiv, Doron; Eyal, Ana; Wolf, Michael; Primov‐Fever, Adi
Abstract : Objective: To enhance knowledge and understanding of the laryngeal framework maturation in different age groups and genders. Study Design: Cohort imaging study. Setting: Tertiary academic referral center. Methods: Computed tomography neck scans of 283 patients aged 8 to 20 years were studied. The interlaminae angle (ILA) of the thyroid cartilage at the level of the vocal folds, the anterior projection (angulation) of the thyroid cartilage (TC), and the degree of calcifications were evaluated and compared in sequential age groups of both genders. Results: Neck scans of 171 males and 112 females were reviewed. The average ILA was 76.45° ± 14.2 and 94.25° ± 10.2 for males and females, respectively ( P  < 10–25). In the female group, the mean angle was relatively constant (91–970) in all age groups, whereas in the male groups the angle decreased with age (920–670) ( r  = −0.9, P  < 0.005) The most significant decrease was measured in the 14‐ to 15‐year age group. The thyroid prominence was significantly more anteriorly angulated in males. The angle in the female age groups was constant (170.1°), and the angle in males decreased with age (161.47°) ( P  = 0.000008). Calcifications were more prominent at the posterior portion of the cartilage in both genders and increased with age. Conclusion: Structural diversities of the TC begin in adolescent males because the thyroid cartilage grows anteriorly with a narrower ILA and with a greater anterior angulation. Our study shows that these changes, along with the degree of laryngeal cartilages calcification in both genders, occur as a continuum throughout puberty. Level of Evidence: 4. Laryngoscope, 127:E354–E358, 2017